Transient atrial fibrillation and risk of stroke after acute myocardial infarction - Bishara, Rema; Telman, Gregory; Bahouth, Fadel; Lessick, Jonathan; Aronson, Doron (Thrombosis and Haemostasis, 2011)
Atrial fibrillation (AF) is a frequent complication of acute myocardial infarction (AMI). In the AMI setting, AF is frequently brief and attributed to acute haemodynamic changes, inflammation or ischaemia. However, it remains uncertain whether transient AF episodes are associated with a subsequent increased risk of ischaemic stroke. We studied the impact of transient new-onset AF on the one-year risk of ischaemic stroke or transient ischaemic attack (TIA) in a retrospective cohort of 2,402 patients with AMI. Patients with previous AF or AF at hospital discharge were excluded. Transient AF occurred in 174 patients (7.2%) during the initial hospitalisation. During one year follow-up after hospital discharge, stroke or TIA occurred in 16 (9.2%) and 58 (2.6%) patients with and without transient AF, respectively (p< 0.0001). Compared with patients without transient AF, the adjusted hazard ratio for stroke or TIA in patients with transient AF was 3.03 (95% CI 1.73–5.32; p< 0.0001). Stroke or TIA occurred in 2.6% of patients without AF, 6.3% of patients with transient AF treated with oral anticoagulants, and 9.9% of patients with transient AF treated with antiplatelet agents. The incidence of recurrent AF after hospital discharge was markedly higher in patients with transient AF during the index hospitalisation (22.8% vs. 2.0%, p< 0.0001). In conclusion, transient AF complicating AMI is associated with an increased future risk of ischaemic stroke and TIA, particularly in patients treated with antiplatelet agents alone. High AF recurrence rates in these patients also suggest that oral anticoagulants should be strongly considered.
Keywords: Atrial fibrillation; myocardial infarction; stroke